Clarity of Procedures and Satisfaction with Online Registration Services: Kejelasan Prosedur dan Kepuasan terhadap Layanan Pendaftaran Online - Mukaromah, Citra Amiliana; Yektiningtyastuti, Yektiningtyastuti; Prodia, Natalia Sabatyaningsih (Procedia of Engineering and Life Science, 2025)
Hospitals play a vital role in providing medical services to the community. In an effort to improve service quality, RSU Aprilia Cilacap has introduced an innovation by implementing an online registration system. This study aims to evaluate the clarity of the registration procedures and patient satisfaction with the online service, as well as to identify obstacles encountered during its implementation. This study used a quantitative approach with a descriptive correlational design. The sampling technique used was consecutive sampling. Data collection was conducted by distributing questionnaires to 38 outpatient respondents. The results indicate that 42.1% of respondents found the online registration procedures unclear, and the same percentage expressed dissatisfaction with the service. Conversely, 34.5% stated that the procedures were very clear, and 39.4% reported being very satisfied with the service. The Rank-Spearman statistical test yielded an r value = 0.835 with a p value = 0.000. This finding indicates a significant relationship between procedural clarity and the level of satisfaction with online outpatient registration at Aprilia Cilacap Hospital. The main obstacles identified include the lack of systematic and comprehensive procedural guidelines and low digital literacy among some patients. Therefore, increasing outreach and education regarding the use of the online registration system is a crucial step in improving the quality of service at Aprilia Cilacap Hospital.